Efektivitas TGT (Team Games Tournament) pada Pembelajaran Responsif Budaya - Faizi, Ahmad; Binur Huda, Muhammad; Hardinanto, Eko; Kholik; Dzarna; Ratu Sholeha, Amanda (Universitas Al-Qolam Malang, 2025)
This study aims to describe the effectiveness of the Team Games Tournament (TGT) learning model in the context of culturally responsive learning. TGT is a game-based learning strategy that is considered capable of accommodating the cultural diversity of students and increasing their active role in the learning process. Through literature studies, data were collected from various scientific articles discussing the implementation of TGT with adaptation to local culture. The analysis was carried out using a descriptive and interpretive approach to describe how the implementation of TGT can create fun, interactive, and meaningful learning. The results of the study showed that TGT was effective in increasing active participation of students, building self-confidence, and making learning experiences more relevant to their cultural background. However, studies related to the meaningfulness of learning activities in a cultural context are still limited, so further research is needed to explore this aspect in more depth.